2022
DOI: 10.3390/nu14030598
|View full text |Cite
|
Sign up to set email alerts
|

Bifidobacterium animalis subsp. lactis A6 Enhances Fatty Acid β-Oxidation of Adipose Tissue to Ameliorate the Development of Obesity in Mice

Abstract: Fatty acid β-oxidation (FAO) is confirmed to be impaired in obesity, especially in adipose tissues. We previously proved that Bifidobacterium animalis subsp. lactis A6 (BAA6) had protective effects against diet-induced obesity. However, whether BAA6 enhances FAO to ameliorate the development of obesity has not been explored. After being fed with high-fat diet (HFD) for 9 weeks, male C57BL/6J mice were fed HFD or BAA6 for 8 weeks. In vitro study was carried out using 3T3-L1 adipocytes to determine the effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 72 publications
0
13
0
Order By: Relevance
“…Previous studies have shown that maternal L. reuteri supplementation alleviated placental oxidative damage induced by maternal HFD and had a positive effect on hepatic steatosis in fetus, which is achieved by recoding key enzymes related to lipid metabolism (Yu et al., 2022). In several other animal studies, it was found that the β‐oxidation in the liver or epididymal adipose tissues of mice was activated by probiotic intervention (Huo et al., 2022; Park et al., 2013; Yoon et al., 2023). In these above studies, PPARα was up‐regulated to varying degrees after probiotic intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that maternal L. reuteri supplementation alleviated placental oxidative damage induced by maternal HFD and had a positive effect on hepatic steatosis in fetus, which is achieved by recoding key enzymes related to lipid metabolism (Yu et al., 2022). In several other animal studies, it was found that the β‐oxidation in the liver or epididymal adipose tissues of mice was activated by probiotic intervention (Huo et al., 2022; Park et al., 2013; Yoon et al., 2023). In these above studies, PPARα was up‐regulated to varying degrees after probiotic intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, Y. Huo et al found that Bifidobacterium animalis subsp. lactis A6 enhances adipose tissue fatty acid β-oxidation (FAO) to mitigate obesity development by increasing acetate levels and activating the GPR43-PPARα signaling pathway in mice [ 5 ].…”
Section: Obesity and Metabolic Disordersmentioning
confidence: 99%
“…Previous studies have shown that all three major SCFAs can promote lipogenic differentiation of 3 T3-L1 pre-adipocytes. Acetate treatment of 3 T3-L1 pre-adipocytes leads to an increase in the expression of genes related to lipogenic differentiation (Huo et al, 2022). Hong et al showed upregulation of peroxisome proliferator-activated receptor-γ (PPAR-γ) and GPR43 mRNA expression in 3 T3-L1 cells treated with acetate or propionic acid for 7 days; this effect was counteracted in the absence of GPR43 (Hong et al, 2005).…”
Section: The Effects Of Short-chain Fatty Acids On Adipose Tissue Met...mentioning
confidence: 99%